Diffusion and Innovation of Islamic Religious Education Curriculum - Boy, La; Obaid, Moh. Yahya; Herman, Herman; Samsuri, Samsuri (RELIGI: Jurnal Pendidikan Agama Islam, 2026)
This study aims to analyze the diffusion and innovation of Islamic Religious Education (PAI) curriculum through a synthesis of innovation diffusion theory and Islamic ecotheological perspectives. The study is grounded in the need to reconstruct the PAI curriculum not merely as a technical or digital innovation agenda, but as an epistemological transformation responsive to social change, ecological crises, and civilizational challenges. This research employed a qualitative approach using a library research design based on conceptual-synthetic analysis. Data were analyzed through content analysis, thematic analysis, and conceptual synthesis to formulate a new theoretical model. The findings reveal that PAI curriculum innovation constitutes a multidimensional transformation encompassing innovation in educational goals, integrative content, transformative pedagogy, and authentic assessment. The success of curriculum innovation is significantly influenced by the effectiveness of innovation diffusion through change agents, communication channels, institutional culture, and adoption mechanisms. This study proposes a novelty in the form of the Integrative Eco-Theological Diffusion Model, which integrates tawhid, khalifah, amanah, and sustainability values as normative inputs, with Islamic value compatibility functioning as a mediating variable in innovation adoption. This model extends classical diffusion of innovation theory by incorporating theological dimensions as a crucial factor in the adoption of curriculum innovation in Islamic education. The study implies that the development of PAI curriculum should move from technology-driven innovation toward value-driven transformative innovation oriented toward sustainability and Islamic civilizational transformation.